Analysis of Sustainable Cultural Tourism Development in Mamasa Regency: Promotion Strategy and Distinctiveness - Rivai, Dian Rahmayanti; Wulandari, Futri Ayu; Irawati (PT. Maju Malaqbi Makkarana, 2025)
Research Aims: The development of sustainable cultural tourism is influenced by several factors, namely the promotion strategy and the distinctiveness of a tourist destination. This research aims to identify and test aspects of promotion strategy and distinctiveness in the analysis of sustainable cultural tourism development in Mamasa Regency through aspects of promotion strategy and distinctiveness. Design/methodology/approach: This research tends to have a qualitative approach and uses an in-depth interview method with an interview guide. This research utilizes Nvivo 14 as the software employed for data analysis, validity testing, and drawing research conclusions. Additionally, to measure validity in this study, triangulation techniques were used. Research Findings: The results of this research show that the development of sustainable cultural tourism in Mamasa Regency requires a careful approach to promoting and utilizing cultural uniqueness. With an effective and sustainable promotional strategy, and using cultural uniqueness as the main attraction, Mamasa Regency can position itself as a superior and attractive cultural tourism destination. Theoretical Contribution/Originality: This research seeks to identify what is needed for planning in organizing and managing the tourism sector to provide maximum contribution to the Mamasa region. Therefore, two aspects are examined: promotion strategies and distinctiveness in the development of cultural tourism.